Instant messaging and presence technologies for college campuses. - Chatterjee, S. (IEEE Network : the magazine of global information exchange)
Instant messaging is an application that enables networked users to send and receive short messages. Presence provides information about users' reachability and willingness to accept/reject a brief chat session. Various proprietary IM and presence (IM&P) solutions are currently on the market, and standards are emerging. There are interoperability problems between the two dominant standards (SIMPLE and XMPP); as a result, this important application is finding difficulty in widespread deployment within college campuses and businesses. We describe a brief history of the development of IM&P technology discuss the current standardization work being done within IETF, and present an overall architecture of emerging standards. We provide a comparison between the SIP/SIMPLE and Jabber/XMPP standards. We also present data and its analysis from a survey of campus organizations that sheds light into the main issues of deploying, managing and provisioning of IM&P services on college campus.